Detection of aeromonas hydrophila using fiber optic sensor - Balakrisnan, Samla Gauri (2015)
Pathogenesis including chronic infections, inflammation, malignancy, tissue break down, and immune system disorder are linked with pathogens that affect human health with massive diseases. Aeromonas hydrophila infections increasingly recognized as a serious worldwide public health concern. Although numerous antibiotics and vaccination have been introduced to protect against diseases, some pathogen continues to threaten living life. However, the current pathogen detection method which based on molecular culture and PCR techniques are fundamentally slow and time consuming. Consequently, these discoveries have created awareness in development of effective pathogen detecting tool to control the related quality and prevent further infections. In recent time, several researchers have attempted to develop rapid detecting tool. Despite advanced engineering, there is still need for an accurate and rapid pathogen detection tool. Thus, this research has been carried out to highlight mostly on detection of Aeromonas hydrophila by using optical biosensor as contribution of this study while Escherichia coli and Saccharomyces cerevisiae were used for justification of the findings as part of the experimental work. In this study, we proposed an optical based biosensor as relatively an accurate method of early effective detection of pathogen or infectious agent. Fiber optic flow cell and fiber optic microchannel were used in this study for detection of pathogens. Fiber optic flow cell was used as preliminary study for optical characteristic of the pathogens used. Then optical microchannel was fabricated with fiber optics by using photolithography method. Fiber optic was chosen as signal receiving and transmitting medium due to its excellent plus rapid signal delivering feature. Fiber optic biosensor is based on light scattering, absorption and optical properties of the microorganisms. The chemical composition, energy, the total nucleotides and photopigments will define the absorption properties of each microorganism. The difference in peak absorbance spectra of microorganism at particular region of wavelength will be manipulated for detection of the sample. Based on the experimental findings, the detection of A.hydrophila and E.coli of any phases (lag,exponential and stationary) were fall in UV spectral region while every phases of S.cerevisiae detection falls in visible spectral region. A.hydrophila was identified at between 350nm to 354nm and E.coli detected at region of 280nm to 285nm by using the microchannel. While, S. cerevisiae recognized in visible region of 570nm to 580nm. The entire detection can be done in less than 10 minutes. These detection regions for each sample have been compared with fiber optic flow cell measurements, spectrophotometer measurement plus theoretical calculations by using Beer Lambert Absorption Law and proved the detection regions were in approximately accurate spectral.